Degradation of tetracycline in water by ultrasonic irradiation. - Wang, Xikui (Water Science and Technology)
The objective of this work is to investigate the effectiveness of ultrasonic radiation for the degradation of tetracycline. We analyzed the influence of several operational parameters, including the solution pH, ultrasonic power, initial concentration of tetracycline, H2O2 addition, and the most common anions in surface waters such as bicarbonate, nitrate and sulfate. The results showed that the ultrasonic degradation of tetracycline followed pseudo first-order kinetics. The tetracycline degradation rate is highly pH-dependent and favored at higher pH. The degradation ratio increased with increasing ultrasonic power density, but decreased with increasing the initial concentration of tetracycline. The addition of bicarbonate ions and H2O2 can enhance the degradation rate. No rate variation was observed with the presence of nitrate and sulfate ions.